Elevated Heme Oxygenase-1 Correlates With Increased Brain Iron Deposition Measured by Quantitative Susceptibility Mapping and Decreased Hemoglobin in Patients With Parkinson’s Disease - Xu, Jinghui; Xiao, Chi; Song, Weizheng; Cui, Xiangqin; Pan, Mengqiu; Wang, Qun; Feng, Yanqiu; Xu, Yunqi (Frontiers in Aging Neuroscience, 2021)
Background: Brain iron deposition, low hemoglobin (HGB) and increased heme oxygenase-1(HO-1) have been implicated in Parkinson's disease (PD). However, the association among them in PD is poorly studied. Objective: To explore the association of the level of HO-1 with brain iron deposition and low level of HGB in PD. Methods: A total of 32 patients with PD and 26 controls were recruited. C57BL/6 male mice were used in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD model. The Levels of serum HO-1and HGB were assayed. Quantitative susceptibility mapping (QSM) was used to quantitatively analyse brain iron deposition. HO-1 inhibitor (Sn-protoporphyrin,SnPP) was used to suppress the function and expression of HO-1. Results: This study revealed significant elevation of the serum HO-1 concentrations, iron deposition within bilateral substantial nigra（SN）, red nucleus, and putamen and decrease of HGB level in PD patients. There was a significantly positive correlation between the serum HO-1 concentration and iron deposition within SN, inverse correlation between the serum HO-1 concentration and HGB level in PD patients. A significant increase in HO-1 expression of serum and iron deposition in SN was also observed in PD mouse model, and the SnPP could significantly reduce iron deposition in the SN. Conclusions: The high level of HO-1 may be the common mechanism of iron deposition and low HGB in PD. Therefore, the findings presented in this study indicate that HO-1 correlate with brain iron deposition and anaemia in PD.